Slang Words Used in Dope Movie - Hanifa Fildza Ghassani; Otong Setiawan Djuharie; Toneng Listiani (Universitas Islam Negeri Palopo, 2025)
This study examines the types and meanings of slang words used in Rick Famuyiwa's